2023
DOI: 10.1111/acel.13802
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal stem cell aging at single‐cell resolution: Transcriptional perturbations alter cell developmental trajectory reversed by gerotherapeutics

Abstract: The intestinal epithelium consists of cells derived from continuously cycling Lgr5hi intestinal stem cells (Lgr5hi ISCs) that mature developmentally in an ordered fashion as the cells progress along the crypt‐luminal axis. Perturbed function of Lgr5hi ISCs with aging is documented, but the consequent impact on overall mucosal homeostasis has not been defined. Using single‐cell RNA sequencing, the progressive maturation of progeny was dissected in the mouse intestine, which revealed that transcriptional reprogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(58 reference statements)
2
2
0
Order By: Relevance
“…4E ). This dietary suppression of cell developmental progression was also reported in mice in which genetic manipulation of mitochondrial structure downregulated stem cell function ( 51 ) and in human patients with IBD ( 36 ), and was also identified by us in aging mice, reversed by geroprotectors ( 56 ).…”
Section: Resultssupporting
confidence: 61%
“…4E ). This dietary suppression of cell developmental progression was also reported in mice in which genetic manipulation of mitochondrial structure downregulated stem cell function ( 51 ) and in human patients with IBD ( 36 ), and was also identified by us in aging mice, reversed by geroprotectors ( 56 ).…”
Section: Resultssupporting
confidence: 61%
“…3c ). These findings are consistent with previous reports (GSE186811) analyzing Lgr5 hi cells from 12-month-old mice with bulk RNAseq which showed >95% of stem cell signature genes were down-regulated at 12 months when compared to 3 months 14 , 15 , which indicated that the stem cells damage appeared as early as middle age (12-month-old mouse) 16 .
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…Another study has revealed that CR preserves the functionality of adult stem cells in the intestinal epithelium by lowering mTORC1 activity, thereby safeguarding ISCs from DNA damage (Bruens et al., 2020). Rapamycin treatment improved the competitive reconstitution ability of aged HSCs, increased the frequency of ISCs and Paneth cells in young mice, partially restored aged mesenchymal stem cells (MSCs) functionality, and delayed the senescence of human epithelial stem cells (Choi et al., 2023; Kawakami et al., 2019; Nie et al., 2021). Studies on various types of stem cells have also shown that CR leads to an increase in stem cell quantity, regenerative potential, and reduced senescence (Bruens et al., 2020; Longo et al., 2021; Maharajan et al., 2020).…”
Section: “Old” Hallmarks Of Aging—longevity Perspectivementioning
confidence: 99%
“…Curcumin, a plant‐derived compound with well‐appreciated anti‐inflammatory properties, has shown variable results in regard to its impact on different stem cell types (N. Wang et al., 2016). Finally, senolytic drugs, including ABT263, dasatinib, and quercetin, have been shown to improve stem cell function by recycling senescent MSCs in mice (Chang et al., 2019; Choi et al., 2023; M. T. Islam et al., 2023).…”
Section: “Old” Hallmarks Of Aging—longevity Perspectivementioning
confidence: 99%